ЖЕНСКИЕ ОБРАЗЫ В РОМАНЕ Д.РУБИНОЙ «НА СОЛНЕЧНОЙ СТОРОНЕ УЛИЦЫ» - Ешниязова, Э.Н. (SCIENCE and SOCIETY, 2022)
This article discusses female images in the novel by the famous writer D. Rubina "On the Sunny Side of the Street". The similarities and differences between the images of mother and daughter are compared, their characteristic features are revealed, the reason for the discord between women is clarified.